Identificação dos parâmetros do modelo de Drucker-Prager/CAP para estudo da densificação mecânica de alumina atomizada - Rocco, Filipe Oliveira (Universidade Federal de São Carlos, 2019)
Pressing followed by sintering is among the most versatile materials processing routes and suits different classes of materials: ceramic, polymeric and metallic. In the last decade, this processing route has been gaining prominence in the industrial scenario. Pressing is a critical step in the process, as any nonhomogeneity introduced during this step is able to adversely affect the mechanical properties of the final (sintered) component. Thereby, the computational simulation of the pressing process is an important tool for the study and optimization of its main parameters. Mainly, the method allows the visualization and optimization of the pressing process before any investment is made in tooling projects and experimental tests. In order to obtain reliable results aided by the finite element method, it is necessary to first adopt a suitable material model for the mechanical compaction of the powder and, secondly, to follow a consistent calibration methodology of this model in order to determine its parameters with precision and consistency. The present work proposed the study of the process of cold pressing of alumina. For this purpose, the Drucker-Prager/Cap model implemented in Abaqus, a commercial finite element software, was used. The main objective of this project is the formulation of an experimental procedure to reliably calibrate the parameters of the constitutive model. The parameters of the model were calibrated by means of an experimental methodology, combining results obtained through different mechanical tests and taking into account the phenomenology of compaction of the particulate materials.
Identification of Drucker-Prager/Cap model parameters for the study of mechanical densification of atomized alumina
Keywords: Prensagem uniaxial; Compactação de pós; Alumina atomizada; Drucker-Prager/Cap; Closed die pressing; Powder compaction; Alumina; Drucker-Prager/Cap; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS